Wife’s Support, Access to Health Services, Availability of Competent Health Personnel and Infrastructure and Intention to Have a Vasectomy for Married Men (Medico Legal Update, 2021)
Family planning (FP) including vasectomy has positive effects in terms of viable socio-economicdevelopment and in reducing maternal deaths. The percentage of married men who use condoms (3%) ishigher than the percentage who choose vasectomy (less than 1%). The study was conducted in the Madiuntown administration using a community-based cross-sectional study design. The town is found in East JavaProvince, Indonesia. The total sample of this study is 323 married man with fixed disease sampling. Age ofwife, wife’s support for vasectomy family planning, access to vasectomy family planning health servicesand availability of health resources and health infrastructure for vasectomy family planning relates to theselection of men to use vasectomy. In general, vasectomy is seen as one of the least preferred method offamily planning and is associated with fear and weakness.